MRI enhanced with ultrasmall superparamagnetic particles of iron oxide in the assessment of cellular inflammation after myocardial infarction. (25th February 2016) - Stirrat, Colin; Alam, Shirjel; MacGillivray, Thomas; Gray, Calum; Dweck, Marc; Mirsadraee, Saeed; Henriksen, Peter; Semple, Scott; Newby, David
Abstract: Background: Macrophages have a central role in the inflammatory response to myocardial infarction and predict subsequent clinical outcome. Ultrasmall superparamagnetic particles of iron oxide (USPIO) are an MRI contrast agent consisting of an iron oxide core surrounded by a dextran coat. They are small enough to migrate passively across the endothelium in regions of inflamed vasculature where they are engulfed by tissue macrophages and can be detected on T2* MRI. We aimed to examine temporal changes in cellular inflammation and tissue oedema in patients after acute myocardial infarction using USPIO-enhanced T2* and T2 mapping MRI. Methods: 31 patients were followed up for 3 months after acute myocardial infarction. Repeated T2* and T2 maps were acquired with 3T MRI immediately before and 24 h after USPIO administration. Regions of interest were categorised into infarct, peri-infarct, and remote myocardial zones, and compared with other organs and tissues. Findings: After one administration, USPIO enhancement was detected by changes in MRI R2* (1/T2*) in non-infarcted myocardium (50/s before enhancement vs 84/s 24 h after administration, p<0·0001), kidney (53 vs 172, p<0·0001), and blood pool (27 vs 124, p<0·0001) at 24 h, bone marrow until 4–9 days (276 vs 533, p<0·0001), and liver and spleen until 13–21 days (72 vs 152 [p=0·0001] and 67 vs 148 [p=0·0354], respectively). Histology confirmed co-localisation of iron and macrophages within infarcted tissue. After repeated administration, increased USPIO enhancement was detected by changes in R2* in the infarct zone, peaking at days 2–3 and persisting until days 10–16 compared with values at 3 months (88·5/s and 65·4 vs 39·5, p<0·0001 and p<0·0372, respectively). By contrast, T2-defined myocardial oedema in the infarct zone peaked at days 3–9 (59 ms) and remained increased at the 3 month follow-up timepoint compared with remote myocardium (49 ms vs 44, p=0·0007). Interpretation: We have shown that myocardial macrophage activity can be detected with USPIO-enhanced MRI in the first 2 weeks after acute myocardial infarction. This pattern of cellular inflammation is distinct from the more prolonged myocardial oedema detectable with T2 mapping. USPIO-enhanced MRI holds promise as a non-invasive method of assessing myocardial cellular inflammation with potential application to diagnosis, risk stratification, and assessment of therapeutic interventions, not only after myocardial infarction but also in other inflammatory conditions affecting the heart. Funding: British Heart Foundation.